PERANCANGAN SISTEM INFORMASI KERJASAMA BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL DI POLITEKNIK PIKSI GANESHA - Alhambra, Kapela; Purnama Putra, Yuliansyah; Suharto, Edi (INFOKOM (Informatika & Komputer), 2024)
A web-based application specifically tailored to facilitate and streamline collaborative endeavors between Politeknik Piksi Ganesha and a diverse array of external collaborators. In this design, the Laravel framework is used as the main framework in building a collaborative information system. The system aims to streamline collaboration with external stakeholders such as industries, companies, educational institutions, government agencies, and other organizations. Through this system, users can access information about available collaboration programs and affiliated partners. The system provides features including user management, collaboration program data management, partner data management, collaboration document management, program search, and data sorting. Additionally, the system is equipped with notification features to keep users updated on ongoing collaborations. The use of the Laravel framework ensures fast, secure, and efficient system development. The collaboration information system is expected to enhance Politeknik Piksi Ganesha's efficiency and effectiveness in establishing partnerships with external parties. It simplifies the overall collaboration process, providing convenience for all stakeholders involved.